Teachers' Strategies to Increase Students' Motivation in Learning English in the First Grade at SMP Negeri 2 Tinambung - Hestika, Hestika; Mahmud, Murni; Nur, Sahril (Journal of Excellence in English Language Education, 2024)
Educators have an important role in educational preparation and learning. Teacher methodology is very important for every educator to achieve progress in his teaching. An instructor is required to have an educational methodology to improve the quality of teaching and learning preparation. In teaching, educators must have technique because it is an important ability to change along with advances in technology in life. Instructions must also be created. Many problems arise in learning, such as students' difficulty in receiving material due to the separation of structures so that they can study well and get good grades. Instructors can encourage students by applying several methodologies. Therefore, teachers must have effective and proficient techniques to encourage their students. Additionally, English dialects may be a difficult subject that not everyone can master. This research aims to determine teacher strategies for increasing students' learning motivation in learning English in the first grade at  SMP Negeri 2 Tinambung. The formulations of the research problems were: (1) What are the teachers’ strategies to increase student motivation in learning English at SMP Negeri 2 Tinambung? (2) How do teachers' strategies contribute to students' motivation to learn English at SMP Negeri 2 Tinambung? In this research, the researcher used a qualitative method. The population is class I students of SMP Negeri 2 Tinambung consisting of 2 English teachers and 10 students. Samples were taken from classes A and D of SMP Negeri 2 Tinambung. The instruments used were observation checklists and interviews. The results show that the teachers’ strategies to increase students' motivation in learning English were very important to increase students' enthusiasm for receiving the material and can increase students' interest in learning English.